Effects of inorganic nitrogen forms on growth, morphology, nitrogen uptake capacity and nutrient allocation of four tropical aquatic macrophytes (Salvinia cucullata, Ipomoea aquatica, Cyperus involucratus and Vetiveria zizanioides) - Jampeetong A. (2014)
This study assesses the growth and morphological responses, nitrogen uptake and nutrient allocation in four aquatic macrophytes when supplied with different inorganic nitrogen treatments (1) NH4+, (2) NO3-, or (3) both NH4+ and NO3-. Two free-floating species (Salvinia cucullata Roxb. ex Bory and Ipomoea aquatica Forssk.) and two emergent species (Cyperus involucratus Rottb. and Vetiveria zizanioides (L.) Nash ex Small) were grown with these N treatments at equimolar concentrations (500 μM). Overall, the plants responded well to NH4+. Growth as RGR was highest in S. cucullata (0.12 ± 0.003 d-1) followed by I. aquatica (0.035 ± 0.002 d-1), C. involucratus (0.03 ± 0.002 d-1) and V. zizanioides (0.02 ± 0.003 d-1). The NH4+ uptake rate was significantly higher than the NO3- uptake rate. The free-floating species had higher nitrogen uptake rates than the emergent species. The N-uptake rate differed between plant species and seemed to be correlated to growth rate. All species had a high NO3- uptake rate when supplied with only NO3-. It seems that the NO3- transporters in the plasma membrane of the root cells and nitrate reductase activity were induced by external NO3-. Tissue mineral contents varied with species and tissue, but differences between treatments were generally small. We conclude, that the free-floating S. cucullata and I. aquatica are good candidate species for use in constructed wetland systems to remove N from polluted water. The rooted emergent plants can be used in subsurface flow constructed wetland systems as they grow well on any form of nitrogen and as they can develop a deep and dense root system. © 2011 Elsevier B.V. All rights reserved.